A Systematic Approach towards Citizen Centric Services Using Digital Governance: Improving Service Quality and Citizen Satisfaction through Citizen-centric Digital Governance (Journal of Advances and Scholarly Researches in Allied Education, 2017)
A citizen centric perspective permits the government to facilitate enhanced service quality which in turn increases citizen satisfaction. It is stated that citizen centric service incorporates designing of services according to the user’s opinion rather than of the government organizations. And so e-governance must be citizen friendly. The primary function of government is the delivery of services to the citizen. Many countries across the world identify good governance as an important goal. Certain specific initiatives have been taken up for open government by these governments. Hence, the freedom of information is re-explored and supported by detailed guidelines. The emergence of Internet has proved to be a powerful tool for good governance initiatives. An essential measure of Internet revolution is the possibility of providing anytime and anywhere services. And a constant effort is made to involve the citizen as the center of focus of governance where citizens are considered as customers and clients. This paper discusses citizen centric e-Governance system and also describes about the citizen centric services.